To the uttermost end : the photographic amalgamation of history, imagination, science and exploration in the seascape : an exegesis presented in partial fulfillment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Kay, Jonathan (Massey University, 2013)
This exegesis is essentially a quest to discover a place that still remains in the realm of the unknown; where imagination and science, history and memory, reality and artifice are all architects of space. Framing this investigation in the locality of the sea, this research explores mythological, scientific and imaginative agents that allow access to concepts of the intangible and unseen. Through photography, To the Uttermost End explores the dichotomy between objectivity and artifice, touching on notions of the technological sublime.
Keywords: Photography; Art installations; Exploration in art; Seascapes